PERFIL COMPORTAMENTAL E DESEMPENHO PROATIVO E REATIVO EM LAMBARI-DO-RABO-AMARELO (ASTYANAX BIMACULATUS) EM ESTÁGIO JUVENIL - GONÇALVES, Isabela Pinto; DALEGRAVE, Caroline de Brito; SILVA, Gabriel dos Santos; SANTOS, Emmanuel Jarsen dos; OLIVEIRA, Fúlvia Cristina; COSTA, Deliane Cristina (ANAIS DO ENIC, 2022)
-